When the British Musical Ruled the World - Sellers, Robert (Rowman & Littlefield Publishers, 2023)
For decades, British stage musicals struggled to compete against the dazzling Broadway productions that came roaring in from across the pond. But that tide was turned at last in 1978, when Tim Rice and Andrew Lloyd Webber’s production of Evita brought the West End back into contention with Broadway. It was just the first of several blockbuster productionsthat helped Britain dominate musical theater all over the world. In this revealing behind-the-scenes narrative, journalist and author Robert Sellers gives a definitive account of how Evita, Cats, Starlight Express, Les Misérables, Phantom of the Opera, Chess, and Miss Saigon changed the business of musical theater in the 1980s. These mega productions of the were larger than life, colorful, and spectacular. Sellers collects insightful, personal stories from cast members, set designers, musical supervisors, dancers, lighting designers, production managers, singers, and choreographers from the shows that finally put Broadway on its back foot. He also describes the backstage drama, production nightmares, and financial woes that threatened to derail the shows at multiple points. Whatever obstacles they faced, though, these productions swept the world and transformed the face of musical theater in ways that still resound today.